Detection Of Geodynamic Events On The Objects Of Agro-Industrial Complex On The Basis Of Phase-Metric Method Of Geo-Ecological Monitoring - Baknin M. D., Surzhik D. I., Kuzichkin O. R., Vasilyev G. S., Kovalenko A. O. (International Journal of Advanced Science and Technology, 2020)
The article considers the principles of detecting geodynamic events at the objects of the agro-industrial complex based on the phase-metric method of geo-ecological control. The problem of registration of geodynamic events that change slowly over time is identified by the example of oil product leaks from area objects of their storage and processing, and the prospects for its solution based on the phase-metric method are shown. An approach to the detection of geodynamic events based on the phase-metric method of geo-ecological monitoring and correlation detection of deterministic signals is proposed. The approach is illustrated by the necessary diagrams and models for the case of processing recorded analog signals from an arbitrary receiving line of the system and using a phase detector based on an analog signal multiplier. For experimental testing of the proposed approach, using a specially developed geoecological monitoring system and a layout model of an area object of the fuel and energy complex, modeling and early detection of oil product leaks were performed, which confirmed the effectiveness and feasibility of the proposed method.